PHATIC EXPRESSIONS ON “EMILY IN PARIS” SERIES - Novita Masing; Sanerita T. Olii; Fivy A. Andries (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study was a descriptive qualitative study. The data was collected from the dialog containing the phatic expression. The forms of Phatic Expressions are evaluated using Jean Aitchison's theory, and the situational context is analyzed using Pragmatics theory by using Holmes' Social Dimension of Communication and Hymes' SPEAKING theory. According to the findings of this study, 181 data used phatic phrases. Names are often used by speakers in the form of phatic expressions. When individuals gather to welcome one another, they exchange ritual words. The speakers used phatic terms such as name. When they are in an embarrassing circumstance, a standard subject of discussion to start a relationship. The speakers used phatic terms such as name. When they praise others, they demonstrate unity and empathy. To break the quiet and preserve social relationships, the speakers used phatic expressions such as name maeningless words or misunderstood words. The background of the moment when the characters used phatic terms on the street, at the restaurant, at the workplace, at the bar party, at the event, on the market, and in public places. It might be professional or casual. Formal situations are common for initial meetings between strangers and opposites